Participação popular e democracia direta pós-1988: todo o poder emana do povo, mas por ele será exercido? - Lima, Camila dos Santos de (2021)
Using a qualitative approach, it is proposed to reflect on what is understood as “participationism” or, precisely, as popular participation in the current constitutional context. The production in question will present, based on data extracted from reality, empirical facts - in this case, the experiences of popular participation since the advent of CF / 88, emphasizing the practical cases of exercise of the institutes of direct democracy - an analysis reflective on the data obtained. Thus, from a methodological point of view, this work will incorporate deductive elements, through the conceptual analysis that is proposed, as well as elements of an inductive nature, considering the proposal for reflection on popular participation based on specific cases taken from reality, which that is, situations in which the mechanisms of direct democracy have been managed. Therefore, the production is divided into four moments, namely: initially a presentation on the concepts of democracy, participation and representation in a historical perspective, revisiting these notions from Antiquity to the contemporary period. Afterwards, this conceptual cut is resumed within Brazilian history and, in the next moment, the context of the 1988 Constitution of the Federative Republic of Brazil, in force, is emphasized. On that occasion, there is a delimitation about concepts such as direct, indirect, semi-direct, participatory and representative democracy, whose confrontation is equally important for the debate proposed in this work. With emphasis on the constitutionally established direct democracy institutes - plebiscite, referendum and popular initiative - the presentation of practical cases, that is, situations in which such mechanisms were handled, starts. Thus, data are brought about the referendum on the Brazilian government system and regime from 1993, the referendum on the prohibition of trade in firearms and ammunition in the country, and the popular initiative that resulted in the creation of the Bill of Law Clean. The final moment is intended, then, for the debate about the concepts brought and their applicability with regard to the presented practical cases, in order to propose an exercise of reflection in what concerns the reality today, both on the promised democracy, as on the mechanisms that would trigger popular sovereignty.